Synergistic effects of titanium dioxide and graphene nanofillers on delamination and thrust forces in machining glass fiber reinforced nanocomposites - Machabhaktuni Sri Harsha; Vennelakanti Sai Hemanth Kumar; Mandapati Bhavani Prasad; Chandrasekar Muthukumar; Senthil Muthu Kumar Thiagamani; Nadir Ayrilmis; Senthilkumar Krishnasamy; Lin Feng Ng; Naveen Jesuarockiam (Scientific Reports)
Abstract Delamination factor in drilling represents the maximum spread of imperfections around the drilled hole in a polymer composite. Df can directly affect the performance of the drilled component. This study focuses on investigating the influence of nanofillers, titanium dioxide and graphene, with epoxy in varying quantities ranging from 1 to 4 wt%, on the delamination behavior of the glass fiber-reinforced composites. The parameters, such as spindle speeds (600, 1200, and 1800 rpm), feed rates (30, 40, and 50 mm/min), and drill bit diameter (4, 6, and 8 mm), were considered. A high-resolution camera was used to capture the images of the drilled hole, which were processed using MATLAB to compute the delamination factor at top and rear faces of the composite. Additionally, thrust force obtained from the dynamometer at various nanofiller quantities was analyzed. The thrust force decreased with an increase in the spindle speed and the feed rate. Spindle speed and feed rate contributed the least to delamination, while filler percentage contributed the least to thrust. The mean GRG showed that GT1, a drill bit diameter of 4 mm, a spindle speed of 1800 rpm and a feed rate of 50 mm/min were the optimum parameters.